2019
DOI: 10.1186/s12943-019-1038-7
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 facilitates tumor progression via an m6A-IGF2BP2-dependent mechanism in colorectal carcinoma

Abstract: Background Colorectal carcinoma (CRC) is one of the most common malignant tumors, and its main cause of death is tumor metastasis. RNA N 6 -methyladenosine (m 6 A) is an emerging regulatory mechanism for gene expression and methyltransferase-like 3 (METTL3) participates in tumor progression in several cancer types. However, its role in CRC remains unexplored. Methods Western blot, quantitative real-time PCR (RT-qPCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
554
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(603 citation statements)
references
References 41 publications
15
554
1
Order By: Relevance
“…In this study, we gradually confirmed that METTL3, a critical m6A methyltransferase, played an oncogenic role in CRC . Moreover, our study and GEO database predicted that up‐regulated expression of METTL3 in CRC tissues was positively associated with overall survival and PFS in patients, which brought light to its potential prognostic value for CRC.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this study, we gradually confirmed that METTL3, a critical m6A methyltransferase, played an oncogenic role in CRC . Moreover, our study and GEO database predicted that up‐regulated expression of METTL3 in CRC tissues was positively associated with overall survival and PFS in patients, which brought light to its potential prognostic value for CRC.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, we gradually confirmed that METTL3, a critical m6A methyltransferase, played an oncogenic role in CRC. 37 Moreover, our study and GEO database predicted that up-regulated expres- as the downstream target of METTL3 in promoting CRC proliferation. One of the main characteristics of malignant tumours is abnormal cell growth.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, although TCGA data showed that abnormal expression of METTL3 may exist in CRC, our knowledge about the link between METTL3 and CRC is still limited. A recent study reported that METTL3 could promote self-renewal of CRC cells through inducing m6A and subsequent upregulation of SOX2 [32]. Similarly, METTL3 and METTL14 also showed opposite effects in the regulation of HCC as above mentioned [11,12].…”
Section: Discussionmentioning
confidence: 88%
“…METTL3 expression was consistently elevated in recurrent colorectal cancer, matched lymph node, and metastatic liver tissues. Colorectal cancer patients with high METTL3 expression had reduced OS and DFS times (37,38). Knockdown of METTL3 in colorectal cancer cells significantly inhibited tumorigenesis and metastasis, cell self-renewal, and the frequency and migration of stem cells in vitro and in vivo (34), suggesting the oncogenic role of METTL3 in colorectal cancer.…”
Section: Mettl3 In Colorectal Cancermentioning
confidence: 99%